Peningkatan kapasitas wanita tani melalui pemanfaatan media online sebagai alat promosi produksi jeruk lahan pasang surut desa sawahan barito kuala - Nurmelati Septiana; Hartoni Hartoni; Karimal Arum Shafriani (Jurnal Abdi Mas Adzkia, 2023)
. Siam Banjar Orange as a leading horticultural commodity on tidal land owned by Barito Kuala Regency, has the potential to be developed for marketing. One way of marketing that can be done easily by farmers is through marketing using online media. Utilizing the capacity of farm women and the outpouring of more time is a potential that can be utilized to increase the promotion of citrus products through online media. The implementation of this service activity uses the Community Based Participatory Action Research (CBPAR) method. The results of the service show that the peasant women in Sawahan Village already have a fairly good capacity with the provision of using online communication and conversation media that they have been utilizing. After this service, peasant women as participants in the service can optimize online media as a means of promoting citrus production. The response of service participants to service activities is quite high, starting from a variability of knowledge, skills and attitudes.